Citra Merek, Kualitas Pelayanan dan Kepercayaan terhadap Keputusan Pembelian E-Commerce Lazada - Yoga Triandi Baso; Hery Pudjoprastyono (IPM2KPE, 2023)
This research aims to determine the influence of brand image, service quality, and trust on Lazada e-commerce purchasing decisions (in people living in Surabaya). The research method uses the Convenience Sampling technique, namely collecting information from members of the population who agree to provide this information directly or indirectly, namely there are 75 samples. The research results show that Brand Image has a positive and significant effect on purchasing decisions. Service quality has a positive and significant effect on purchasing decisions. Trust has a positive and significant effect on purchasing decisions. Keywords: Brand Image, Service Quality, Trust, Purchasing Decisions